Preparation method of high-density crystal nucleus assembled spherical beta-TCP powder for additive manufacturing
By combining water bath heating and spray drying, dense spherical β-TCP powder was prepared, which solved the problem of poor fluidity and dispersion of calcium and phosphorus ceramic powder in 3D printing, and improved the overall consistency and mechanics of the print piece Performance, suitable for artificial bone stents and ceramic 3D printing.
Patent Information
- Application Number
- CN202411393538.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, calcium-phosphorus ceramic powders have problems such as poor slurry fluidity, uneven powder dispersion, low solid content and complex firing process during the 3D printing process, especially the irregular morphology of β-tricalcium phosphate and The structure is loose, resulting in poor overall consistency of the print.
The method of combining heating reaction with spray drying in a pot of water bath is used to control the temperature and time to nucleate the calcium and phosphorus sources into fine grains in the water bath, and act with the binder under the spray drying parameters to form dense spherical β. -TCP powder solves the problems of fluidity and dispersion of powder.
The spherical β-TCP powder with high density crystal core assembly has good fluidity and dispersion, and improves the solid content and overall consistency of 3D printing paste. It is suitable for artificial bone stents and ceramic 3D printing fields.
Smart Images

Figure CN119191831A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of 3D printing powder preparation, and relates to a method for preparing spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing. Background Art
[0002] 3D printing technology has the advantage of customizing ceramics with nano- and macro-features, significantly expanding the application of ceramic materials in a wide range of key technology fields, including aviation, microelectronics, and bone repair materials. During the digital light processing process, polymerization-induced phase separation of resins produces materials with nanoscale morphology, which are composed of ceramic precursors or polymers. However, there are still many problems in the process of 3D printing ceramic materials, such as poor slurry fluidity, uneven dispersion of ceramic powders, low solid content, and complex firing process. In recent years, researchers have found that structural design and surface modification of ceramic powders can effectively improve the flow properties of slurries and improve the overall consistency of printed parts.
[0003] Calcium phosphate ceramic materials have good biocompatibility and osteoinductive properties, and have achieved good osteogenesis when used as tissue engineering scaffold materials. In particular, β-tricalcium phosphate plays an important role in bone mechanical properties and bone regeneration, and its biodegradation rate is close to that of human bone inorganic minerals, while it is difficult for bioinert ceramics to completely imitate the composition and structure of calcium phosphate.
[0004] The thermal sintering of the printed parts produces ceramics with complex macroscopic geometries and nanoscale porosity, which show uniformly distributed through-holes. The degraded calcium and phosphorus ions can enter the circulatory system to participate in the formation of new bone and are eventually replaced by new bone tissue, thus becoming the main research object in the field of bone tissue repair. This method provides a valuable technical platform for the simplified preparation of nanostructured ceramics with complex shapes.
[0005] The Chinese patent "A method for preparing tricalcium phosphate for bio-skeleton materials" (application number: CN202211442466.8, authorization number: CN114074933B, announcement date: 2023.04.18) discloses a method for preparing tricalcium phosphate for bio-skeleton materials. First, phosphoric acid and calcium carbonate are used as raw materials, and high-purity β-TCP nanopowder is obtained by aging, grinding, filter pressing, drying and screening, but the process is complicated, the equipment cost is high, a lot of manual operation is required, and automated production is impossible.
[0006] The Chinese patent "A method for preparing highly hydrated β-tricalcium phosphate for 3D printing" (application number: CN202010833371.3, authorization number: CN114074933B, announcement date: 2023.04.18) discloses a method for preparing highly hydrated β-tricalcium phosphate for 3D printing. First, rare earth materials, titanium sources, calcium salts, etc. are used as raw materials to obtain negatively charged titanium-containing layered silicates through high-temperature hydrothermal reactions; then, it is used as a template to guide phosphoric acid and calcium carbonate to react at high temperatures to obtain hydrated and hardened β-TCP nanopowders, but the resulting product has a loose structure and contains many impurities that cannot be removed. The process is complicated and the preparation cost is high, so it cannot be applied on a large scale.
[0007] The Chinese patent "A method for preparing nano-β-tricalcium phosphate" (application number: CN201610216468.3, authorization number: CN105883742B, announcement date: 2016.08.24) discloses a method for preparing nano-β-tricalcium phosphate. First, a soluble calcium salt is mixed with ethanolamine and phosphate, and then calcined in a muffle furnace to obtain tricalcium phosphate. The process is simple and easy to operate, but the resulting product has an irregular morphology and a large difference in particle size, which reduces the fluidity of the powder and cannot be evenly dispersed in the 3D printing slurry. Summary of the invention
[0008] The present invention aims to invent a simple method of preparing a spherical β-TCP assembled with high-density crystal nuclei for additive manufacturing by combining a one-pot water bath heating reaction with spray drying. The precursor is nucleated into fine grains in a water bath reaction at a certain temperature and time, and then the grains are assembled with a binder under certain spray drying parameters to form a microsphere morphology. By regulating the reaction system, reaction temperature and time, and spray drying parameters, the problem of irregular morphology of calcium phosphate and difficulty in uniform dispersion of powder in the prior art, resulting in low fluidity of 3D printing slurry and poor overall consistency of printed parts, is solved.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] A method for preparing spherical β-TCP powder assembled by high-density crystal cores for additive manufacturing is specifically implemented according to the following steps:
[0011] Step 1, preparing a calcium phosphate precursor solution: dissolving a calcium source and a phosphorus source in deionized water respectively, heating the calcium source mixed solution in a water bath, adding dropwise the phosphorus source mixed solution, stirring for reaction, and then aging.
[0012] Step 2, preparing a spray drying slurry: drying the suspension obtained in step 1, dispersing it in deionized water, adjusting the slurry concentration, and adding an organic binder;
[0013] Step 3, spray drying and powder preparation: placing the slurry obtained in step 2 into a peristaltic pump, selecting appropriate air volume, spray temperature and pressure, adjusting the feed speed of the peristaltic pump, spray drying, and collecting the obtained precursor powder;
[0014] Step 4, calcination: calcining the precursor powder obtained in step 3 to obtain dense spherical powder.
[0015] In the above technical solution, the calcium source mixed solution prepared in step 1 is composed of the following substances by mass percentage: 2% to 20% calcium source, 80% to 98% deionized water, and the sum of the above components is 100%. The calcium source is one of calcium hydroxide and calcium carbonate.
[0016] In the above technical solution, the phosphorus source mixed solution prepared in step 1 is composed of the following substances by mass percentage: 1% to 15% phosphorus source, 85% to 99% deionized water, and the sum of the above components is 100%. The phosphorus source is one of phosphoric acid and diammonium hydrogen phosphate.
[0017] In the above technical solution, the water bath treatment in step 1 is: temperature 55-100°C, time 0.5-6h, and aging time 12-36h.
[0018] In the above technical solution, in step 2, the slurry concentration is 50-200 g / L, the mass ratio of the binder to the powder is 1%, and the added binder is one of PVA, PEG, and PVP.
[0019] In the above technical solution, the spray drying parameters in step 3 are: air volume 3-6m 3 / min, spray temperature 160~260℃, pressure 2~3Bar, feed rate 800~2000mL / h.
[0020] In the above technical solution, the calcination treatment in step 4 is as follows: the precursor powder obtained in step 3 is calcined at 700-900° C. and kept warm for 1-4 hours to obtain a spherical β-TCP powder assembled with high-density crystal cores.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention provides a method for preparing a spherical β-TCP powder assembled with high-density crystal nuclei for additive manufacturing, using calcium hydroxide and calcium carbonate as calcium sources, phosphoric acid and diammonium hydrogen phosphate as phosphorus sources, and reacting in a low-temperature (≤100°C) water bath to achieve uniform growth of crystal nuclei and obtain crystal grains with good crystallization. Then, by spray drying, the crystal grains are self-assembled to form spherical precursor particles. After heat treatment, a spherical β-TCP powder assembled with high-density crystal nuclei is obtained, which has a high sphericity rate (>95%), dense crystal nuclei, and concentrated particle size distribution (3-8μm accounts for ~70%).
[0023] 2. The β-TCP synthesized in the present invention is a spherical powder assembled by high-density crystal nuclei. It is a sphere self-assembled by fine crystals, has good fluidity, better dispersibility during the printing slurry configuration process, and effectively improves the solid content and consistency of the printing material.
[0024] 3. The equipment used in this preparation process is a mature set of equipment from experimental to industrial level. The preparation process is simple, the raw materials used are cheap and easy to obtain, the reaction is a water system that is more environmentally friendly, and the process is stable and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Powder XRD pattern prepared for Example 1.
[0026] Figure 2 This is a scanning electron microscope image of β-TCP prepared in the example.
[0027] Figure 3 This is the scanning electron micrograph of β-TCP in the control group.
[0028] Figure 4 This is the nitrogen adsorption-desorption curve of Example 4.
[0029] Figure 5 This is the nitrogen adsorption-desorption curve of the control group.
[0030] Figure 6 This is the particle size distribution diagram of Example 4.
[0031] Figure 7 This is the particle size distribution diagram of the control group.
[0032] Figure 8 This is the printed support of the β-TCP powder prepared in Example 4.
[0033] Fig. 9 Stress-strain diagram for DLP printed bracket.
[0034] Fig.10 Schematic diagram of the preparation method of the present invention DETAILED DESCRIPTION
[0035] The purpose of the present invention is to provide a method for preparing spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing, which solves the problems in the prior art that the morphology of calcium phosphate is irregular and the powder distribution is uneven, resulting in low fluidity of 3D printing slurry and poor overall consistency of printed parts.
[0036] Combine the following Figure 1-Figure 10 The present invention is further described in detail with reference to the accompanying drawings and specific embodiments.
[0037] The present invention provides a method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing, which is specifically implemented according to the following steps:
[0038] Step 1, prepare the precursor solution: dissolve the calcium source and the phosphorus source in deionized water respectively. The calcium source mixed solution is composed of the following substances by mass percentage: 2% to 20% calcium source, 80% to 98% deionized water, and the sum of the above components is 100%. The calcium source is one of calcium hydroxide and calcium carbonate. The phosphorus source mixed solution is composed of the following substances by mass percentage: 1% to 15% phosphorus source, 85% to 99% deionized water, and the sum of the above components is 100%. The phosphorus source is one of phosphoric acid and diammonium hydrogen phosphate. Heat the calcium source mixed solution in a water bath at 55 to 100°C for 0.5 to 6h, add the phosphorus source mixed solution dropwise, stir to react, and then age;
[0039] Step 2, preparing a spray drying slurry: drying the suspension obtained in step 1 at 60° C., controlling the slurry concentration to be 50-200 g / L, and adding a binder selected from the group consisting of PVA, PEG, and PVP, with the mass ratio of the binder to the powder being 1%;
[0040] Step 3, spray drying powder making: Place the slurry obtained in step 2 into a peristaltic pump, set the feed rate to 800-2000 mL / h, and adjust the air volume to 3-6 m 3 / min, spray temperature 160℃~260℃, pressure 2~3Bar, spray drying, and collect the precursor powder;
[0041] Step 4, calcination treatment: calcine the precursor powder obtained in step 3 at 700-900° C. for 1-4 hours to obtain dense spherical powder.
[0042] The present invention selects environmentally friendly calcium and phosphorus sources, dissolves them and controls the heating temperature and time under water bath heating conditions to densify the crystal nucleus, providing a mild and uniform heating environment, which is conducive to the uniform growth of crystals and the densification of the crystal nucleus. By adjusting the slurry concentration and the binder, the powder is combined and dense, and the mechanical properties of the subsequent printed parts are improved; by adjusting the spray drying parameters, solid spheres with uniform particle size distribution are obtained, the fluidity of the powder is increased, and the powder is evenly dispersed in the printed slurry and is not easy to settle, which improves the consistency of the slurry fluidity and the printed scaffold, and obtains a bone implant scaffold with excellent mechanical properties.
[0043] The present invention makes full use of the characteristics of stable and uniform crystal nucleus growth by water bath heating, and crystallizes the crystal nucleus during its growth process to achieve crystal nucleus densification; by adjusting the concentration of the binder and the slurry, a spherical precursor powder with uniform particle size distribution and high density is obtained under the preferred spray drying parameters; and then a spherical β-TCP assembled with high-density crystal nuclei is obtained by calcination. The spherical powder assembled with high-density crystal nuclei has good fluidity and dispersibility, and can be applied to the preparation process of 3D printing slurry, effectively improving the solid content and uniformity of the printed material, and achieving consistency in the overall performance of the printed part. It has broad application prospects in the fields of personalized customization of artificial bone scaffolds and related ceramic 3D printing.
[0044] The purpose of the present invention is to provide a method for preparing a spherical β-TCP powder assembled with high-density crystal nuclei for additive manufacturing, which solves the problem in the prior art that the irregular morphology of calcium phosphate and uneven distribution of powder lead to low fluidity of 3D printing slurry and poor overall consistency of printed parts. The present invention discloses a method for preparing a spherical β-TCP (β-tricalcium phosphate) powder assembled with high-density crystal nuclei for additive manufacturing, specifically: firstly, a green and environmentally friendly calcium source and a phosphorus source are selected, and the powder is prepared into a precursor powder under water bath heating conditions to regulate the growth of crystal nuclei; secondly, a ceramic precursor, a polymer and a solvent are mixed and stirred to obtain a spray-dried slurry, which is spray-dried to obtain a spherical precursor assembled with crystal nuclei; finally, a spherical β-TCP assembled with high-density crystal nuclei is obtained after calcination.
[0045] Example 1
[0046] Step 1, dissolving 20g of calcium hydroxide in 80g of deionized water, dissolving 15g of diammonium hydrogen phosphate in 85g of deionized water, heating the calcium hydroxide mixed solution in a water bath at 55°C, adding diammonium hydrogen phosphate solution dropwise, stirring for 6h, and then aging to obtain a precursor solution;
[0047] Step 2, drying the suspension at 60° C., controlling the slurry concentration to 50 g / L, and adding 0.5 g PVA to obtain a spray-dried slurry;
[0048] Step 3: Place the spray-dried slurry obtained in step 2 into a peristaltic pump, set the feed rate to 800 mL / h, and adjust the air volume to 3 m 3 / min, spray temperature 160°C, pressure 2Bar, spray drying, and collecting the obtained precursor powder;
[0049] Step 4, calcining the precursor powder at 700° C. for 1 hour to obtain dense spherical powder.
[0050] Example 2
[0051] Step 1, dissolving 10 g of calcium carbonate in 90 g of deionized water, dissolving 20 g of phosphoric acid in 80 g of deionized water, heating the calcium carbonate mixed solution in a water bath at 100° C., adding a phosphoric acid solution dropwise, stirring for 0.5 h, and then aging to obtain a precursor solution;
[0052] Step 2, drying the suspension at 60°C, controlling the slurry concentration to 200 g / L, and adding 2 g of PVP to obtain a spray-dried slurry;
[0053] Step 3: Place the spray-dried slurry into a peristaltic pump, set the feed rate to 2000 mL / h, and adjust the air volume to 6 m 3 / min, spray temperature 260°C, pressure 3Bar, spray drying, and collecting the obtained precursor powder;
[0054] Step 4, calcining the precursor powder at 750° C. for 4 hours to obtain dense spherical powder.
[0055] Example 3
[0056] Step 1, dissolving 15 g of calcium carbonate in 85 g of deionized water, dissolving 15 g of diammonium hydrogen phosphate in 85 g of deionized water, heating the calcium carbonate mixed solution in a water bath at 80° C., adding a phosphoric acid solution dropwise, stirring for 6 hours, and then aging to obtain a precursor solution;
[0057] Step 2, drying the suspension at 60°C, controlling the slurry concentration to 150 g / L, and adding 1.5 g PVP to obtain a spray-dried slurry;
[0058] Step 3: Place the spray-dried slurry into a peristaltic pump, set the feed rate to 1200 mL / h, and adjust the air volume to 4 m 3 / min, spray temperature 200°C, pressure 2Bar, spray drying, and collecting the obtained precursor powder;
[0059] Step 4, calcining the precursor powder at 850° C. for 3 h to obtain dense spherical powder.
[0060] Example 4
[0061] Step 1, dissolving 15 g of calcium hydroxide in 85 g of deionized water, dissolving 20 g of phosphoric acid in 80 g of deionized water, heating the calcium hydroxide mixed solution in a 70° C. water bath, adding a phosphoric acid solution dropwise, stirring for 6 hours, and then aging to obtain a precursor solution;
[0062] Step 2, drying the suspension at 60°C, controlling the slurry concentration to 100 g / L, and adding 1 g PEG;
[0063] Step 3: Place the spray-dried slurry into a peristaltic pump, set the feed rate to 1500 mL / h, and adjust the air volume to 5 m 3 / min, spray temperature 180°C, pressure 3Bar, spray drying, and collecting the obtained precursor powder;
[0064] Step 4, calcining the precursor powder at 900° C. for 2 h to obtain dense spherical powder.
[0065] Figure 1 It is the X-ray diffraction diagram of Example 1 of the present invention. The physical phase shows that the main product is β-phase TCP, and the preparation of calcium phosphate microspheres is achieved. By comparing Example 4 with the control group, it can be seen that after water bath treatment, the XRD diffraction peak intensity of the obtained product is higher than that of the control group, and the crystal nucleus crystallization is better, which is beneficial to improve the mechanical properties of the subsequent 3D printed stent.
[0066] Figure 2 This is a scanning electron microscope image of the dense spherical β-TCP prepared by the present invention. Figure 3 By comparing the spray-dried β-TCP in the control group, it can be seen that the spherical β-TCP obtained by spray drying after water bath heating has fine grains, small pore size, uniform sphericity, and a tight bonding surface. The β-TCP obtained without water bath heating has loose bonding and is easy to break, with bone-like grains bonded together and larger pores.
[0067] like Figure 4 As shown, the nitrogen adsorption and desorption curves in Example 4 of the present invention are Figure 5 The pore size of the control group was significantly reduced.
[0068] like Figure 6 As shown, it is a particle size distribution diagram in Example 4 of the present invention, and Figure 7 By comparison, it can be found that the particle size of the embodiment is significantly larger than that of the control group, which proves that spray drying can make the particles more compact and dense when the grains are finer, and the particle size of the obtained solid spheres that are not easy to break is concentrated in the range of 3-10 μm.
[0069] like Figure 8 As shown, the ceramic compression standard part obtained by DLP printing of the powder in Example 4 of the present invention, the stress-strain curve of the national standard compression test result is as follows Fig. 9 As shown, compared with the control group, the lattice structure of Example 4 is tighter, the combination of grain boundaries and grains is better, so the compressive strength is higher, it is not easy to crack during the test, and the material has better performance.
[0070] Table 1 Performance comparison of β-TCP in the embodiment and the control group
[0071]
[0072] From the comparison in Table 1, it can be seen that the powder prepared in Example has a smaller pore volume and pore size, which proves that the spherical powder has a high density, is more compact, and spray drying obtains β-TCP with a larger particle size. The mechanical properties of the bracket were tested after DLP photocuring printing. The compressive strength of the material in Example 4 was significantly higher than that of the control group. The sphericity of the powder calculated by Avizo reached 97.25%.
[0073] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing spherical β-TCP powder assembled by high-density crystal cores for additive manufacturing, characterized in that: Please follow the steps below to implement: Step 1: Preparation of calcium phosphate precursor solution Dissolve the calcium source and the phosphorus source in deionized water respectively, heat the calcium source mixed solution in a water bath, add the phosphorus source mixed solution dropwise, stir to react, and then age; Step 2, preparing spray drying slurry The suspension obtained in step 1 is dried, dispersed in deionized water, the slurry concentration is adjusted, and an organic binder is added; Step 3: Spray drying and powder making Place the slurry obtained in step 2 into a peristaltic pump, select appropriate air volume, spray temperature and pressure, adjust the feed speed of the peristaltic pump, perform spray drying, and collect the obtained precursor powder; Step 4: Calcination The precursor powder obtained in step 3 is calcined to obtain dense spherical powder.
2. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The calcium source mixed solution prepared in step 1 is composed of the following substances by mass percentage: 2% to 20% calcium source, 80% to 98% deionized water, and the sum of the above components is 100%. The calcium source is one of calcium hydroxide and calcium carbonate.
3. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The phosphorus source mixed solution prepared in step 1 is composed of the following substances by mass percentage: 1% to 15% phosphorus source, 85% to 99% deionized water, and the sum of the above components is 100%. The phosphorus source is one of phosphoric acid and diammonium hydrogen phosphate.
4. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The water bath treatment in step 1 is as follows: temperature 55-100° C., time 0.5-6 h, and aging time 12-36 h.
5. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The slurry concentration in step 2 is 50-200 g / L, the mass ratio of the binder to the powder is 1%, and the added binder is one of PVA (polyvinyl alcohol), PEG (polyethylene glycol), and PVP (polyvinyl pyrrolidone).
6. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The spray drying parameters in step 3 are: air volume 3-6m 3 / min, spray temperature 160~260℃, pressure 2~3Bar, feed rate 800~2000mL / h.
7. The method for preparing a spherical β-TCP powder assembled by high-density crystal nuclei for additive manufacturing according to claim 1, characterized in that: The calcination treatment in step 4 is as follows: calcining the precursor powder obtained in step 3 at 700-900° C. and keeping the temperature for 1-4 hours to obtain a spherical β-TCP powder with high-density crystal core assembly.
Citation Information
Patent Citations
A method for preparing nano-β-tricalcium phosphate
CN105883742B
A method for preparing highly hydrated β-tricalcium phosphate for 3D printing
CN114074933B
Preparation method of tricalcium phosphate for biological framework material
CN118056783A
Micro-sphere hole strontium hydroxylapatite and homogeneous precipitation synthesis process thereof
CN109485026A
Bone repair material as well as preparation method and application thereof
CN112843332A
